Axially loaded single threaded rod glued in glubam joint. (30th May 2020) - Li, T.Y.; Shan, B.; Xiao, Y.; Guo, Y.R.; Zhang, M.P.
Highlights: A series of pull-pull tests on glubam specimens with glued-in threaded rod were conducted to investigate the bond behavior and bond stress distribution. The influence of the anchorage length, drill-hole diameter, slenderness ratio, edge distance and glue-line thickness were evaluated and analyzed. A strength model for the glued-in threaded in glubam was proposed for design purposes. Abstract: Glued-in steel rod is known as strong and very efficient connection in withstanding high forces utilized in modern timber structures. In order to apply this connection for the glued laminated bamboo (glubam) joints, a series of investigations were performed on the single glued-in threaded rod in glubam in this study. Total seventeen groups, each including six identical glubam specimens with glued-in threaded rod parallel to the longitudinal bamboo strip (fiber) direction, were tested to failure in the pull-pull configuration. It is observed that the specimens exhibited four different failure modes, including two types of shear failure at different interfaces. The study revealed that the bond stress distribution of glued-in threaded rod in glubam was not uniform, larger near two ends and smaller in the middle zone. The influence of the anchorage length, drill-hole diameter, bonding length-diameter ratio, edge distance and glue-line thickness were evaluated, and the correlations between each parameter and the shear strength were discussed. Design proposals were also provided, including that the lower limit of edge distance can be taken as 2.3 times of the threaded rod diameter, and the glue-line thickness should not be more than 2 mm. Meanwhile, analytical results showed that the existing models for the glued-in rod in timber cannot be directly applied to calculate the strength of the glued-in threaded rod in glubam. Based on the findings in current study, a strength model for the glued-in threaded in glubam was suggested.